Supplementary material 6. Dalyellia callvucurai Damborenea, Brusa & Noreña, 2007. Confocal image stack (29 pictures) in transversal view - Arias, Abril Agustina (2025)
Supplementary material 6. Dalyellia callvucurai Damborenea, Brusa and Noreña, 2007. Confocal image stack (29 pictures) in transversal view, running from left to right (Video mp4). The organs of genital system are pointed out in the scanning. The color code is the same as in Supplementary Material 4.